Anesthesia for nonintubated video-assisted thoracic surgery. Issue 1 (February 2017) - Sunaga, Hiroshi; Blasberg, Justin D.; Heerdt, Paul M.
Abstract : Purpose of review: This review focuses primarily on nonintubated video-assisted thoracic surgery (NIVATS), and discusses advantages, indications, anesthetic techniques, and approaches to intraoperative crisis management. Recent findings: Advancements in endoscopic, endovascular, and robotic techniques have expanded the range of surgical procedures that can be performed in a minimally invasive fashion. For thoracic operations in particular, video-assisted thoracic surgery (VATS) has largely replaced traditional thoracotomy, and continued technical development has made surgical access into the pleural space even less disruptive. As a consequence, the need for general anesthesia and endotracheal intubation has been re-examined, such that regional or epidural analgesia may be sufficient for cases where lung collapse can be accomplished with spontaneous ventilation and an open hemithorax. This concept of NIVATS has gained popularity, and in some centers has now expanded to include procedures involving placement of multiple ports. Although still relatively uncommon at present, a small number of randomized trials and meta-analyses have indicated some advantages, suggesting that NIVATS may be a desirable alternative to general anesthesia with endotracheal intubation for specific indications. Summary: Although anesthesia for NIVATS is associated with some of the same risks as general anesthesia with endotracheal intubation, NIVATS can be successfully performed in carefully selected patients.